Relevansi Kebijakan Bantuan Sosial pada Kabupaten/Kota di Pulau Sumatera Selama Pandemi Covid-19 - Zulfiqar, Faisal Labib; Maulana, Muhammad Ilham; Abrori, Ali (Jurnal Pajak dan Keuangan Negara (PKN), 2024)
Sumatra Island contributes 23% of Indonesia's GDP but has been among the regions most severely impacted by the COVID-19 pandemic. Both central and local governments have distributed social assistance to mitigate these effects; however, such assistance's benefits remain debatable. This study aims to examine the impact of the COVID-19 pandemic on economic growth and assess how social protection spending moderates this relationship in Sumatra. Additionally, related variables such as education and health expenditures are analyzed. The research employs a quantitative approach using Moderated Regression Analysis (MRA) on 544 year-sample data points from 136 regencies/cities in Sumatra from 2018 to 2021. The findings reveal that the COVID-19 pandemic significantly and negatively affects economic growth. Social protection spending has a significant positive effect on economic growth, while education and health expenditures do not show a significant impact. Furthermore, the interaction between social protection spending and the COVID-19 pandemic yields a significant positive effect.